Corneal Decellularization: A Method of Recycling Unsuitable Donor Tissue for Clinical Translation?. (2nd June 2016) - Wilson, Samantha L.; Sidney, Laura E.; Dunphy, Siobhán E.; Dua, Harminder S.; Hopkinson, Andrew
Abstract: Background : There is a clinical need for biomimetic corneas that are as effective, preferably superior, to cadaveric donor tissue. Decellularized tissues are advantageous compared to synthetic or semi-synthetic engineered tissues in that the native matrix ultrastructure and intrinsic biological cues including growth factors, cytokines and glycosaminoglycans may be retained. However, there is currently no reliable, standardized human corneal decellularization protocol. Methods : Corneal eye-bank tissue unsuitable for transplantation was utilized to systematically compare commonly used decellularization protocols. Hypertonic sodium chloride; an ionic reagent, sodium dodecyl sulphate; a non-ionic detergent, tert-octylphenol polyoxyethylene (Triton-X); enzymatic disaggregation using Dispase; mechanical agitation; and the use of nucleases were investigated. Decellularization efficacy, specifically for human corneal tissue, was extensively evaluated. Removal of detectable cellular material was evidenced by histological, immunofluorescence and biochemical assays. Preservation of macroscopic tissue transparency and light transmittance was evaluated. Retention of corneal architecture, collagen and glycosaminoglycans was assessed via histological, immunofluorescence and quantitative analysis. Biocompatibility of the resulting scaffolds was assessed using cell proliferation assays. Results : None of the decellularization protocols investigated successfully removed 100% of cellular components. The techniques with the least residual cellular material were most structurally compromised. Biochemical analysis of glycosaminoglycans demonstrated the stripping effects of the decellularization procedures. Conclusion : The ability to utilize, reprocess and regenerate tissues deemed "unsuitable" for transplantation allows us to salvage valuable tissue. Reprocessing the tissue has the potential to have a considerable impact on addressing the problems associated with cadaveric donor shortage. Patients would directly benefit by accessing greater numbers of corneal grafts and health authorities would fulfill their responsibility for the delivery of effective corneal reconstruction to alleviate corneal blindness. However, in order to progress, we may need to take a step back to establish a "decellularization" criterion; which should balance effective removal of immune reactive material with maintenance of tissue functionality.